Coexistence of local structural heterogeneities and long-range ferroelectricity in Pb-free (1_x)Ba(Zr0.2Ti0.8)</mml: - K. Dey; A. Ahad; K. Gautam; A. Tripathy; S. S. Majid; S. Francoual; C. Richter; M. N. Singh; A. Sagdeo; E. Welter; N. Vittayakorn; V. G. Sathe; et al. (My University, 2021)
Environmentally benign (1-x)Ba(Ti$_{0.8}$Zr$_{0.2}$)O$_3$-x(Ba$_{0.7}$Ca$_{0.3}$)TiO$_3$ (BZT-BCT) ceramics are promising materials due to their remarkable high piezoresponse [Liu and Ren, Phys. Rev. Lett. \textbf{103}, 257602 (2009)]. In this Letter, by focusing on local and average structure in combination with macroscopic electromechanical and dielectric measurements we demonstrate the structure property relationship in the tetragonal BZT-BCT ceramic. During high-temperature cubic to tetragonal phase transformation, polar nanoregions are manifested through the spontaneous volume ferroelectrostriction at temperatures below $\sim$ 477 K. Temperature-dependent local structural investigations across the Zr K edge extended x-ray absorption fine structure spectroscopy reveal an anomalous collaboration between the ZrO$_{6}$ and TiO$_6$ octahedra. These octahedra compromise their individuality during polarization development. The presence of domains of submicron size embedded inside the macroscopic ferroelectric regions below T$_{m}$, as well as their hierarchical arrangement, is observed by piezo-response force microscopy. Effects of the existence of the structural/polar heterogeneities below T$_{m}$ are observed also when polarizibilities of the poled and the unpoled samples are compared; the poled sample is found to be more susceptible to the electric field. In addition, by using electric field dependent x-ray diffraction studies we also show that this ceramic under field exhibits reduction of tetragonal distortion, which is consistent with earlier reports.
Keywords: Ferroelectric and Piezoelectric Materials